Age‐related changes to macrophages are detrimental to fracture healing in mice. Issue 3 (25th February 2020) - Clark, Daniel; Brazina, Sloane; Yang, Frank; Hu, Diane; Hsieh, Christine L.; Niemi, Erene C.; Miclau, Theodore; Nakamura, Mary C.; Marcucio, Ralph
Abstract: The elderly population suffers from higher rates of complications during fracture healing that result in increased morbidity and mortality. Inflammatory dysregulation is associated with increased age and is a contributing factor to the myriad of age‐related diseases. Therefore, we investigated age‐related changes to an important cellular regulator of inflammation, the macrophage, and the impact on fracture healing outcomes. We demonstrated that old mice (24 months) have delayed fracture healing with significantly less bone and more cartilage compared to young mice (3 months). The quantity of infiltrating macrophages into the fracture callus was similar in old and young mice. However, RNA‐seq analysis demonstrated distinct differences in the transcriptomes of macrophages derived from the fracture callus of old and young mice, with an up‐regulation of M1/pro‐inflammatory genes in macrophages from old mice as well as dysregulation of other immune‐related genes. Preventing infiltration of the fracture site by macrophages in old mice improved healing outcomes, with significantly more bone in the calluses of treated mice compared to age‐matched controls. After preventing infiltration by macrophages, the macrophages remaining within the fracture callus were collected and examined via RNA‐seq analysis, and their transcriptome resembled macrophages from young calluses. Taken together, infiltrating macrophages from old mice demonstrate detrimental age‐related changes, and depleting infiltrating macrophages can improve fracture healing in old mice. Abstract : Delayed fracture healing in old mice is associated with transcriptomic differences between old and young macrophages infiltrating the fracture callus. An aged macrophage phenotype was characterized by increased pro‐inflammatory gene expression compared to young. Inhibition of macrophage infiltration in old mice improved fracture healing outcomes and demonstrated a resident macrophages population with a transcriptome more similar to young mice.